Pengaruh Motivasi Kerja dan Lingkungan Kerja terhadap Kinerja Karyawan PT Tembaga Mulia Semanan Tbk - Dinah Arifah; Isyana Emita (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2026)
As a manufacturing company engaged in the processing of copper and wire products, PT Tembaga Mulia Semanan, Tbk requires human resources with optimal performance to support the achievement of organizational goals. This study aims to examine the effect of work motivation and work environment on employee performance at PT Tembaga Mulia Semanan, Tbk. This research employed a quantitative approach with data collection conducted through questionnaire distribution. The research population consisted of all employees of the South Continuous Rod (SCR) Division, totaling 65 employees, with a sample of 42 respondents. The collected data were analyzed using multiple linear regression analysis with the assistance of SPSS software. The results of the t-test indicate that work motivation partially has a positive and significant effect on employee performance, as shown by a t-value of 4.265 which is greater than the t-table value of 2.022, with a significance level of 0.000 < 0.05. The work environment also partially has a positive and significant effect on employee performance, indicated by a t-value of 6.080 which is greater than the t-table value of 2.022 and a significance value of 0.000 < 0.05. Furthermore, the F-test results show that work motivation and work environment simultaneously have a positive and significant effect on employee performance. The coefficient of determination (R²) of 63.52% indicates that variations in employee performance can be explained by work motivation and work environment, while the remaining percentage is influenced by other factors outside this study.